Community's House Yards Utilization Education in Support of the Green City - Lensari, Delfy; Rosianty, Yuli; Yuningsih, Lulu; Hustati, Sasua; Puspitasari, Meika (Altifani Journal: International Journal of Community Engagement, 2021)
Community awareness was needed in realizing the sustainability of urban life. This community concern can be done in realizing a green city. A Green City is an environmentally friendly city by reducing waste, effectively utilizing water and energy resources, implementing an integrated information system, and synergizing the natural and artificial environment. The purpose of this KKN-55 collaborative service activity is to provide an understanding to the community about planting can help government programs in P2KH (Green City Development Program), participate in protecting the environment and, build community motivation to want to plant trees or other plants in the yard of the house and maintain existing green open spaces. This collaborative service activity between lecturers and KKN-55 students was carried out online on February 20, 2021. The service target is people who live in RT 13 Sriwijaya Village, Tungkal Ilir District, Tanjung Jabung Barat Regency, Jambi Province, both men and women who have home gardens who have a desire to plant. The implementation of this activity was attended by 37 participants enthusiastically which was marked by many questions, participants are also motivated to take advantage of the home page by planting trees, ornamental plants, vegetables, and so on so that they can increase their income.